Muscle LIM Protein Force-Sensing Mediates Sarcomeric Biomechanical Signaling in Human Familial Hypertrophic Cardiomyopathy. Issue 16 (6th April 2022) - Riaz, Muhammad; Park, Jinkyu; Sewanan, Lorenzo R.; Ren, Yongming; Schwan, Jonas; Das, Subhash K.; Pomianowski, Pawel T.; Huang, Yan; Ellis, Matthew W.; Luo, Jiesi; Liu, Juli; Song, Loujin; et al.
Abstract : Background: Familial hypertrophic cardiomyopathy (HCM) is the most common inherited cardiac disease and is typically caused by mutations in genes encoding sarcomeric proteins that regulate cardiac contractility. HCM manifestations include left ventricular hypertrophy and heart failure, arrythmias, and sudden cardiac death. How dysregulated sarcomeric force production is sensed and leads to pathological remodeling remains poorly understood in HCM, thereby inhibiting the efficient development of new therapeutics. Methods: Our discovery was based on insights from a severe phenotype of an individual with HCM and a second genetic alteration in a sarcomeric mechanosensing protein. We derived cardiomyocytes from patient-specific induced pluripotent stem cells and developed robust engineered heart tissues by seeding induced pluripotent stem cell–derived cardiomyocytes into a laser-cut scaffold possessing native cardiac fiber alignment to study human cardiac mechanobiology at both the cellular and tissue levels. Coupled with computational modeling for muscle contraction and rescue of disease phenotype by gene editing and pharmacological interventions, we have identified a new mechanotransduction pathway in HCM, shown to be essential in modulating the phenotypic expression of HCM in 5 families bearing distinct sarcomeric mutations. Results: Enhanced actomyosin crossbridge formation caused by sarcomeric mutations in cardiac myosin heavy chain ( MYH7 ) led to increased force generation, which, when coupled with slower twitch relaxation, destabilized the MLP (muscle LIM protein) stretch-sensing complex at the Z-disc. Subsequent reduction in the sarcomeric muscle LIM protein level caused disinhibition of calcineurin–nuclear factor of activated T-cells signaling, which promoted cardiac hypertrophy. We demonstrate that the common muscle LIM protein–W4R variant is an important modifier, exacerbating the phenotypic expression of HCM, but alone may not be a disease-causing mutation. By mitigating enhanced actomyosin crossbridge formation through either genetic or pharmacological means, we alleviated stress at the Z-disc, preventing the development of hypertrophy associated with sarcomeric mutations. Conclusions: Our studies have uncovered a novel biomechanical mechanism through which dysregulated sarcomeric force production is sensed and leads to pathological signaling, remodeling, and hypertrophic responses. Together, these establish the foundation for developing innovative mechanism-based treatments for HCM that stabilize the Z-disc MLP-mechanosensory complex.